Tribology of electroless nickel coatings – A review - Sahoo, Prasanta; Das, Suman Kalyan (Materials in engineering, 2011)
Electroless coating is different from the conventional electrolytic coating as the former does not require any electricity for its operation. The advantages include uniform coating and also nonconductive materials can be coated. Electroless nickel coatings possess splendid tribological properties such as high hardness, good wear resistance and corrosion resistance. For this reason, electroless nickel has found wide applications in aerospace, automobile, electrical and chemical industries. Quest for improved tribological performances has led many researchers to develop and investigate newer variants of electroless nickel coatings like Ni–W–P, Ni–Cu–P, Ni–P–SiC, Ni–P–TiO2, and so on. Also the enhancement of tribological characteristics through modification of the coating process parameters has remained a key point of interest in researchers. The technological advancement demands the development of newer coating materials with improved resistance against wear and tear. Electroless nickel has shown huge potential to fit in that space and so the study of its tribological advancement deserves a thorough and exhaustive study. The present article reviews mainly the tribological advancement of different electroless nickel coatings based on the bath types, structure and also the tribo testing parameters in recent years.